LDL Receptor Gene-ablated Hamsters: A Rodent Model of Familial Hypercholesterolemia With Dominant Inheritance and Diet-induced Coronary Atherosclerosis - Xin Guo; Mingming Gao; Yunan Wang; Xiao Lin; Liu Yang; Nathan Cong; Xiangbo An; Feng Wang; Kai Qu; Liqing Yu; Yuhui Wang; Jinjie Wang; et al. (EBioMedicine, 2018)
Familial hypercholesterolemia (FH) is an autosomal dominant genetic disease caused mainly by LDL receptor (Ldlr) gene mutations. Unlike FH patients, heterozygous Ldlr knockout (KO) mice do not show a dominant FH trait. Hamsters, like humans, have the cholesteryl ester transfer protein, intestine-only ApoB editing and low hepatic cholesterol synthesis. Here, we generated Ldlr-ablated hamsters using CRISPR/Cas9 technology. Homozygous Ldlr KO hamsters on a chow diet developed hypercholesterolemia with LDL as the dominant lipoprotein and spontaneous atherosclerosis. On a high-cholesterol/high-fat (HCHF) diet, these animals exhibited severe hyperlipidemia and atherosclerotic lesions in the aorta and coronary arteries. Moreover, the heterozygous Ldlr KO hamsters on a short-term HCHF diet also had overt hypercholesterolemia, which could be effectively ameliorated with several lipid-lowering drugs. Importantly, heterozygotes on 3-month HCHF diets developed accelerated lesions in the aortas and coronary arteries. Our findings demonstrate that the Ldlr KO hamster is an animal model of choice for human FH and has great potential in translational research of hyperlipidemia and coronary heart disease.